Enhanced activity of multiple TRIC‐B channels: an endoplasmic reticulum/sarcoplasmic reticulum mechanism to boost counterion currents - O'Brien, F; Eberhardt, D; Witschas, K; El-Ajouz, S; Iida, T; Nishi, M; Takeshima, H; Sitsapesan, R; Venturi, E (Wiley, 2019)
KEY POINTS:There are two subtypes of trimeric intracellular cation (TRIC) channels but their distinct single-channel properties and physiological regulation have not been characterized. We examined the differences in function between native skeletal muscle sarcoplasmic reticulum (SR) K+ -channels from wild-type (WT) mice (where TRIC-A is the principal subtype) and from Tric-a knockout (KO) mice that only express TRIC-B. We find that lone SR K+ -channels from Tric-a KO mice have a lower open probability and gate more frequently in subconducting states than channels from WT mice but, unlike channels from WT mice, multiple channels gate with high open probability with a more than six-fold increase in activity when four channels are present in the bilayer. No evidence was found for a direct gating interaction between ryanodine receptor and SR K+ -channels in Tric-a KO SR, suggesting that TRIC-B-TRIC-B interactions are highly specific and may be important for meeting counterion requirements during excitation-contraction coupling in tissues where TRIC-A is sparse or absent. ABSTRACT:The trimeric intracellular cation channels, TRIC-A and TRIC-B, represent two subtypes of sarcoplasmic reticulum (SR) K+ -channel but their individual functional roles are unknown. We therefore compared the biophysical properties of SR K+ -channels derived from the skeletal muscle of wild-type (WT) or Tric-a knockout (KO) mice. Because TRIC-A is the major TRIC-subtype in skeletal muscle, WT SR will predominantly contain TRIC-A channels, whereas Tric-a KO SR will only contain TRIC-B channels. When lone SR K+ -channels were incorporated into bilayers, the open probability (Po) of channels from Tric-a KO mice was markedly lower than that of channels from WT mice; gating was characterized by shorter opening bursts and more frequent brief subconductance openings. However, unlike channels from WT mice, the Po of SR K+ -channels from Tric-a KO mice increased as increasing channel numbers were present in the bilayer, driving the channels into long sojourns in the fully open state. When co-incorporated into bilayers, ryanodine receptor channels did not directly affect the gating of SR K+ -channels, nor did the presence or absence of SR K+ -channels influence ryanodine receptor activity. We suggest that because of high expression levels in striated muscle, TRIC-A produces most of the counterion flux required during excitation-contraction coupling. TRIC-B, in contrast, is sparsely expressed in most cells and, although lone TRIC-B channels exhibit low Po, the high Po levels reached by multiple TRIC-B channels may provide a compensatory mechanism to rapidly restore K+ gradients and charge differences across the SR of tissues containing few TRIC-A channels.